Analysis of Academic Hardiness Factors Affecting Student Emotional Exhaustion in Malang Using Logit and Probit Models - Nuradilla, Siti (Jurnal Matematika, Statistika dan Komputasi, 2024)
The prevalence of emotional exhaustion as an indication of academic burnout among students during online learning is very high. Responding to the issues and neglect of studies on academic burnout, it is necessary to analyze the factors of academic hardiness among students in Malang City regarding emotional exhaustion. The ordinal probit regression model yields the best fit with 120 samples in analyzing the factors of academic hardiness on emotional exhaustion due to its smaller AIC value. Significant factors affecting emotional exhaustion are commitment to academic tasks (), control over struggle (), and control individual difficulties (). The ordinal probit regression model obtained is and . The marginal effect states that for every one-unit change in the ratio will increase students low emotional exhaustion by 0.016, and decrease students moderate emotional exhaustion by 0.044, and high emotional exhaustion by 0.060. Every one-unit change in the ratio will decrease students low emotional exhaustion by 0.018, and increase students moderate emotional exhaustion by 0.049, and high emotional exhaustion by 0.067. Every one-unit change in the ratio will increase students low emotional exhaustion by 0.025, and decrease students moderate emotional exhaustion by 0.070, and high emotional exhaustion by 0.095.